SULPHURIC ACID LEACHING OF LOW/MEDIUM GRADE Mn ORES USING A NOVEL NITROGENEOUS REDUCTANT- NH3NH2HSO4 (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Low and medium grade land as well sea based manganese ores were used for manganese extraction in H2SO4 -NH3NH2HSO4 (hydrazine sulphate) medium For land based Mn ores, only Mn recovery is important but for sea nodules which contain substantial amounts Co, Ni, and Cu, their recovery is equally important.  In the present studies four samples used were: Indian ocean manganese nodules, medium and low grade Mn ores of Gujarat, and low grade Mn ore of Orissa, India. The Mn content of these ores varied from 15 to 39%. The objective of this work is to establish a reductant which can be used for leaching Mn from all types of ores. The optimum conditions established for nodules by varying parameters such as time, temperature, pulp density, H2SO4 and NH3NH2HSO4 concentrations were: pulp density 10%, time 0.5h, temperature 110oC, NH3NH2HSO4 3.25 g/10g, H2SO4 2.0% (v/v) for 96.9% Mn, 85.25% Cu, 92.58% Ni and 76.5% Co extractions. More than 92% Mn could be leached from different types of ores by varying amount of reductant and acid concentration at 35oC. Depending on Mn content 1.0 to 1.2 times stochiometric amount of reductant and 1.5 to 1.8 times sulphuric acid were required for >92% Mn extraction.